In vivo Antihypertensive and Antihyperlipidemic Effects of the Crude Extracts and Fractions of Moringa stenopetala (Baker f.) Cufod. Leaves in Rats - Geleta, Bekesho; Makonnen, Eyasu; Debella, Asfaw; Tadele, Ashenif (Frontiers in Pharmacology, 2016)
Moringa stenopetala (Baker f.) Cufod. is a medicinal plant that has been used in Ethiopian traditional medicine as a remedy for treatment of hypertension and diabetes. The aim of this study was to evaluate antihypertensive and antihyperlipidemic effect in fructose induced hypertensive rats. Rats were randomly divided into control and treatment groups (n=6). Treatment groups were given daily extracts (250, 500, and 1000 mg/kg) orally with fructose. Whereas, positive, negative and normal control groups were received captopril (20 mg/kg/day with fructose), only fructose (66% w/v ad libitum) and distilled water ad libitum for 15 days, respectively. The blood pressure was measured every 5th day using tail cuff blood pressure analyzer, and on the 16th day the blood was sampled to evaluate antihyperlipidemic effect using clinical chemistry analyzer. The study showed that aqueous and 70% ethanol extracts significantly prevented blood pressure increment in a dose dependent manner comparable to that of the standard drug. Similarly, the extracts suppressed increment in lipid profile (cholesterol, glucose and triglycerides) compared with negative control. The biochemical test revealed that extracts produced a rise in liver but no effect on kidney function indicators compared with normal control. These findings revealed that both crude extracts of Moringa stenopetala (Baker f.) Cufod. possess antihypertensive and antihyperlipidemic effect.